A Comparative Study of Impact Effect of Composite Cylinders and Type IV Pressure Vessels. Issue 1 (17th March 2021) - Farhood, Naseer H; Karuppanan, Saravanan; Ya, Hamdan H; Abdul-Lateef, Wisam A
Abstract : Generally, composites are sensitive to transverse impact loading because there is no through thickness reinforcement for these materials. Specifically, type IV composite pressure vessels and cylinders are more susceptible under the impact loading because of the presence of plastic liner. The main challenges related to the existing composite pressure vessels materials are low toughness, low damage tolerance and high cost. Fiber hybridization is one of the active strategies employed to toughen composites and improve impact damage resistance. Therefore, in this paper, low velocity impact resistance and induced damage severity of carbon-basalt/epoxy hybrid composites were experimentally studied on different cylinders, under 100 J impact energy. The potential of these new hybrid composites was analyzed for type IV pressure vessels. The composite cylinders with eight cylindrical laminates of different stacking sequence and fiber content ratios were fabricated through the filament winding technique. The damage characterization was evaluated using SEM technique for both composite cylinders and pressure vessels. The results indicated that, basalt/epoxy samples exhibited better impact resistance, energy absorption and lower damage severity than carbon/epoxy samples for both composite cylinders and type IV pressure vessels. Besides, hybrid composite pressure vessels exhibited better impact performance compared to the pure carbon/epoxy vessel.